Analysis Of Hydrocarbon Gas Combustion Processes Through CFD Modeling Based On Theoretical And Experimental Approaches - Savriyev Sh.Sh. (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The growing demand for energy resources, the need for environmental safety, and the improvement of fuel efficiency have made the in-depth study of hydrocarbon gas combustion processes a pressing issue. These processes directly determine not only the generation of thermal energy but also the amount of exhaust gases produced. In particular, increasing the efficiency of combustion, gaining a deeper understanding of heat transfer mechanisms, and developing environmentally compliant technologies require a modern scientific and technical approach.